Demolition works at Jalan Sengkang, Pekan Pagoh, Muar, Johor / Mohd Nizham Aziz - Aziz, Mohd Nizham (2016)
Demolition is divided into 5 chapter which is introduction, literature review, case study, problem and recommendations and conclusion. For the chapter 1 are introduction about the background of industrial training Muar Municipal Council. In addition, in this chapter also shows the logo, vision and mission of Majlis Perbandaran Muar (MPM). Chpater 1 has two organizations chart which is organization of Majlis Perbandaran Muar (MPM) headed by the Yang Dipertua Majlis Perbandaran Muar and organization of building department headed by architect J44. Chapter 1 also have about the scope of work in the from public employees to the Yang Dipertua Majlis Perbandaran Muar. To make it easier to identify where industry practice, in this chapter have one of the key plan, location plan and site plan. Next, the chapter 2 about literature view in demolitions work. Chapter 2 have introduction and definition about demolition works. In addition, there are 5 important sub chapter in chapter 2 which is planning, utilities, hazardous material, precautionary measures and method of demolition. Planning is the works before to start demolition works. Utilities consists of the electricity, water and so on. Hazardous material is hazardous goods such as asbestos containing material and soil contamination material. Sub chapter 4 which is an important precautionary measures associated with these precautions to avoid any accident occurred during the demolition works are in progress. There are 6 ways in sub chapter method of demolition to make demolition works on a building. 6 method demolition works are top down manner by manual method, top down by machines, mechanical method by hydraulic crusher with long boom arm, wrecking ball, implosion and other methods. There are 2 by law of demolish works in chapter 2 which is the street, drainage and building act 1974 act 133 and town and country planning act 1976. Chapter 3 is the chapter on case studies located in Jalan Sengkang, Pekan Pagoh, Muar, Johor. There are two departments involved in this case study the internal departments of Majlis Perbandaran Muar (MPM) and external departments which are police, SAJ, TNB and 1 contractors who carry 8 out these works demolish the building Nuswarna Sdn Bhd in Jalan Sengkang Pekan Pagoh, Muar, Johor. There are 2 machinery used to demolish this work, which are 2 backhoe and 2 tipper. To make it easier to identify where this case study, there are 3 plan that is key plan, location plan and site plan. Moreover, in chapter 3, there are a flowchart of demolish work and examples letter, memo and notices for demolish work in subheadings Process works at Jalan Sengkang, Pekan Pagoh, Muar, Johor. Chapter 4 tells about the problem and recommendation on the case studies in Jalan Sengkang, Pekan Pagoh, Muar, Johor. There are 2 problems and 2 recommendations provided in this case study, which can be fixed to demolish work in the future. Finally, Chapter 5 are about the methods and processes of the work done by the Majlis Perbandarana Muar (MPM).